Treatment with Linezolid or Vancomycin in Combination with Rifampin Is Effective in an Animal Model of Methicillin-Resistant Staphylococcus aureus Foreign Body Osteomyelitis - Vergidis, Paschalis (American Society for Microbiology (ASM), 2011)
Rifampin monotherapy was compared to the combination of linezolid or vancomycin with rifampin in an experimental rat model of methicillin-resistant Staphylococcus aureus (MRSA) chronic foreign body osteomyelitis. MRSA was inoculated into the proximal tibia, and a titanium wire was implanted. Four weeks after infection, rats were treated intraperitoneally for 21 days with rifampin alone (n = 16), linezolid plus rifampin (n = 14), or vancomycin plus rifampin (n = 13). Thirteen animals received no treatment. At completion of treatment, qualitative cultures of the wire and quantitative cultures of the bone (reported as median values) were performed. Quantitative cultures from the control, rifampin monotherapy, linezolid-plus-rifampin, and vancomycin-plus-rifampin groups revealed 4.54, 0.71, 0.10, and 0.50 log(10) CFU/gram of bone, respectively. The bacterial load was significantly reduced in all treatment groups compared to that in the control group. Rifampin resistance was detected in isolates from 10, 2, and 1 animal in the rifampin, linezolid-plus-rifampin, and vancomycin-plus-rifampin groups, respectively. Cultures of the removed wire revealed bacterial growth in 1 and 2 animals in the rifampin and linezolid-plus-rifampin groups, respectively, with no growth in the vancomycin-plus-rifampin group and growth from all wires in the untreated group. In conclusion, we demonstrated that combination treatment with linezolid plus rifampin or vancomycin plus rifampin is effective in an animal model of MRSA foreign body osteomyelitis in the context of retention of the infected foreign body.